Teacher Candidates’ Consistency of Physical Quantities Representation in Kinematics: Basic Level - Fathoroni Fathoroni; Imran Imran (Indonesian Journal of STEM Education, 2019)
In the world of physics education, there are still many inconsistencies in the representation of physical quantities in daily delivery, both in written and oral. But not many researches are really focused on the issue, so that research was done to understand the consistency of the basic level of physical scale and its representation on the kinematics. The research has been done by mixed method of embedded correlational design model. The study participants amounted to 20 students in the 3rd semester who have passed the basic physics courses 1. The data were collected using physical consistency knowledge consistency test and its representation, consisting of 7 questions with chain answers. Quantitative data analysis used descriptive analysis and qualitative data analysis used data reduction and interpretation. The result of data analysis shows that consistency of knowledge base level representation of physical quantity consisting of consistency of basic knowledge and consistency of basic use physical quantity and its representation still low. The result of the data analysis shows the consistency of knowledge of physical quantity and the use of representation of physical quantity, all students are at level 5 / LCLV5 (low consistency level 5).